Uji Biologis Konsumsi Pakan, Populasi Bakteri Rumen dan pH Pellet Complete Calf Starter pada Pedet Friesian Holstein Pra Sapih - Nadia Maharani; Joelal Achmadi; Sri Mukodiningsih (Jurnal Agripet, 2015)
(Biological test feed intake, population rumen bacteria and ph pellet complete calf starter friesian holstein on pre weaning calf)ABSTRACT. The study aims to assess the quality of the formula Complete Calf Starter (CCS) with 5% molasses instead of milk to the development of rumen microbial calf Holstein Friesian (HF) pre-weaning. The material used is 20 head calf FH pre weaning age of 2 weeks. Feed intake data taken from 20 respondents consisted of 16 females and 4 calf tail male calf. Data rumen bacterial populations and pH were taken from 5 head of cattle slaughtered at the age of 2 weeks (one tail), 4 weeks (2-tailed) and 6 weeks (2-tailed). The study was designed as a descriptive non-parametric. Parameters measured were rumen bacterial populations, pH and feed intake. The results showed the average consumption of dry matter (DM) and CCS calf milk FH ages 2, 4, 6 weeks respectively at 506, 517, 528 grams. Rumen bacterial populations in calves aged 2, 4, and 6 weeks of 80x106, 45x106 and 19x106 kol/m. ruminal pH in calves aged 2, 4 and 6 weeks was 5.71, 5.36 and 5.55. Biological test showed that the use of complete calf starter (CCS) in the form of pellets FH calves at the age of 2 weeks to stimulate the development of the rumen (feed intake, the population of bacteria and pH) but not in calves aged 4 and 6 weeks. This is because the number of bacterial populations declined due to impaired absorption is impaired absorption of VFA marked low rumen pH.